PENGARUH EFIKASI DIRI WIRAUSAHA, SIKAP DALAM NIAT BERIRAUSAHA DAN FAKTOR LINGKUNGAN - Isma Dwi Ardiyanti (FKIP Unswagati, 2025)
This research aims to analyze the influence of entrepreneurial self-efficacy, entrepreneurial attitudes, and environmental factors on entrepreneurial intentions of students in the Economic Education Study Program, Surabaya State University. The background to this research is based on the low level of entrepreneurship in Indonesia which only reaches 0.18% compared to neighboring countries such as Malaysia which reaches 2%. The research used a quantitative approach with a survey method by distributing questionnaires to 105 respondents who were selected using a simple random sampling technique. Data analysis used multiple linear regression with the help of SPSS 27. The results showed that self-efficacy (β=0.364, p<0.05) and entrepreneurial attitude (β=0.605, p<0.05) had a positive and significant effect on entrepreneurial intentions, while environmental factors (β=0.118, p>0.05) had no significant effect. Simultaneously, the three variables contributed 77.1% to students' entrepreneurial intentions. These findings imply the importance of developing entrepreneurship education programs that focus on increasing self-efficacy and forming positive attitudes towards entrepreneurship. This research provides theoretical contributions in the development of entrepreneurship literature and practical contributions for educational institutions in designing effective student entrepreneurship development programs. Keywords: Entrepreneurial self-efficacy, Entrepreneurial attitudes, and environmental factors on entrepreneurial intentions of students.